The case against sugar ebook - Taubes, Gary (2016)
From the best-selling author of Why We Get Fat, a groundbreaking, eye-opening exposé that makes the convincing case that sugar is the tobacco of the new millennium: backed by powerful lobbies, entrenched in our lives, and making us very sick. Among Americans, diabetes is more prevalent today than ever; obesity is at epidemic proportions; nearly 10% of children are thought to have nonalcoholic fatty liver disease. And sugar is at the root of these, and other, critical society-wide, health-related problems. With his signature command of both science and straight talk, Gary Taubes delves into Americans' history with sugar: its uses as a preservative, as an additive in cigarettes, the contemporary overuse of high-fructose corn syrup. He explains what research has shown about our addiction to sweets. He clarifies the arguments against sugar, corrects misconceptions about the relationship between sugar and weight loss; and provides the perspective necessary to make informed decisions about sugar as individuals and as a society.